ASPEK SUMBERDAYA MANUSIA DALAM PENGEMBANGAN AGRIBISNIS HORTIKULTURA - Totok Mardikanto (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2008)
Considering aspect of human resources more being of adaptive in development of important horticulture agribisnis is immediately paid attention. This matter is caused to realize real human resources being of organizer and determinant of efficacy from each; every effort horticulture agribisnis. Progress in technological innovation of production for the type of this agribisnis will become without effect without beforehand the existence of renewal at human being aspect.